Penerapan Standar Akuntansi Syariah untuk Menilai Kinerja Keuangan Baitul Maal wat Tamwil (BMT) di Lasusua, Kolaka Utara - Iren Iren; Andika Rusli; Sultan Sultan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the application of Islamic accounting standards in assessing the financial performance of Baitul Maal wat Tamwil (BMT) in Lasusua, North Kolaka. The research method used is a qualitative approach with data collection techniques involving observation, interviews, and documentation of BMT’s financial statements for the years 2022–2024. The results of the study indicate that BMT Lasusua has utilized accounting software for recording financial transactions; however, the application of Sharia accounting standards has not yet fully complied with the Sharia PSAK, particularly regarding the recording of murabahah financing. The murabahah practice is conducted through a mechanism where the customer purchases the goods themselves and submits a receipt as proof of the transaction, which indicates the application of murabahah bil wakalah but is not yet administratively optimal. Furthermore, the 8% profit-sharing system lacks a clearly defined profit-sharing ratio, thereby affecting income stability. This situation impacts the quality of financial reports and the assessment of BMT performance, which are not yet fully accurate and transparent in accordance with Sharia principles.